Facet dependence of leakage current and carrier concentration in m‐plane GaN Schottky barrier diode fabricated with MOVPE. Issue 8 (4th July 2017) - Tanaka, Atsushi; Barry, Ousmane1; Nagamatsu, Kentaro; Matsushita, Junya; Deki, Manato; Ando, Yuto; Kushimoto, Maki; Nitta, Shugo; Honda, Yoshio; Amano, Hiroshi
Abstract : In this study, GaN m‐plane Schottky barrier diodes fabricated with a metalorganic vapor‐phase epitaxy on a GaN substrate were investigated using emission microscope, photoluminescence, and cathodoluminescence. In addition, facet dependence of leakage current under reverse‐biased condition was observed. We showed that the leakage‐current distribution was caused by the facet dependence of the carrier concentration and oxygen concentration. These results can provide important suggestions for the fabrication of m‐plane devices. (a) four‐faceted hillocks on m‐plane GaN MOVPE sample, facet dependence of (b) leakage current and (c) PL peak intensity of the m‐plane GaN Schottky barrier diode.